2020
DOI: 10.1111/add.15155
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol use disorder among individuals who binge eat: a systematic review and meta‐analysis

Abstract: Background and Aims Binge eating disorder (BED) is correlated with substance use. This study aimed to estimate the life‐time prevalence of alcohol use disorder (AUD) among individuals with non‐compensatory binge eating and determine whether their life‐time prevalence of AUD is higher than in non‐bingeing controls. Design A systematic search of databases (PubMed, Embase and Web of Science) for studies of adults diagnosed with BED or a related behavior that also reported the life‐time prevalence of AUD was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 70 publications
2
17
0
1
Order By: Relevance
“…Epidemiological studies have revealed a high comorbidity between AUD and overeating pathologies such as obesity and binge-eating disorder (BED) [ 39 ]. Many obese and BED patients have difficulties restraining from consuming palatable foods (high in fat, sugar and/or salt content) and engage in compulsive behaviors similar to those observed in substance abuse disorder [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have revealed a high comorbidity between AUD and overeating pathologies such as obesity and binge-eating disorder (BED) [ 39 ]. Many obese and BED patients have difficulties restraining from consuming palatable foods (high in fat, sugar and/or salt content) and engage in compulsive behaviors similar to those observed in substance abuse disorder [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Less is known clinically, however, about the potential for HFD consumption to increase EtOH intake. Cross-sectional studies report that binge eating behaviors, which can be associated with increased propensity for obesity, are not only associated with increased intake of food higher in energy density, but also increased consumption of EtOH (Muñoz-Pareja et al, 2013 ; Bogusz et al, 2021 ). There are many shared mechanisms between binge eating disorders and drug addiction, including alterations in reward signaling and emotional processing (Carlier et al, 2015 ; Schulte et al, 2016 ; Moore et al, 2017a , b ), which suggests that binging may be part of an overall compulsive behavioral phenotype that can straddle reward modalities.…”
Section: Potential Central Mechanisms Of High Fat Diet and Alcohol Bementioning
confidence: 99%
“…Many previous studies have linked trait impulsivity to binge eating behaviors in clinical patients with BED ( 20 , 21 ). Nevertheless, these samples always had high comorbidity with attention-deficit/hyperactivity disorder (ADHD) ( 22 ), anxiety disorders ( 23 ), and substance use disorders ( 24 ), which might lead to confounding results when detecting the relationship between impulsivity and BED. Moreover, limited data on the associations of trait impulsivity and BED have been incongruous among general populations.…”
Section: Introductionmentioning
confidence: 99%